KAJIAN STILISTIKA: ANALISIS GAYA BAHASA DALAM LIRIK LAGU “QESSET HOBB” RAMY AYACH - Arsal, Fathur Riyadhi; Supianudin, Asep; Wiwaha, Rizzaldy Satria (Program Studi Pendidikan Bahasa Arab Unisda Lamongan, 2024)
Language gives birth to beautiful literary works when composed with the right diction. Currently, many Arabic songs are viral on social media. The virality of Arabic songs is due to several factors, including music genres, arrangements, and expressions of feelings that contain language styles. Using a qualitative methodology, the researchers provided descriptive explanations for the discussion's outcomes. The read-note approach is then used to evaluate the acquired data. Specifically, by carefully reading and hearing the words to Qesset Hobb songs and comprehending the significance of each phrase. Then recording the majas found and categorizing them using Keraf's stylistic theory. Then, interpreting the meaning of the song lyrics to get a picture of the storyline and language style in it related to the data source, then drawing conclusions from the data that has been analyzed. According to the findings of this study, there are at least 13 different varieties of majas, separated into 9 rhetorical majas and 4 metaphorical. Overall, the song